2020
DOI: 10.3103/s1541308x20030048
|View full text |Cite
|
Sign up to set email alerts
|

Radiation-Dominated Implosion with Flat Target

Abstract: Inertial Confinement Fusion is a promising option to provide massive, clean, and affordable energy for humanity in the future. The present status of research and development is hindered by hydrodynamic instabilities occurring at the intense compression of the target fuel by energetic laser beams. A recent proposal by Csernai et al. 1 combines advances in two fields: detonations in relativistic fluid dynamics and radiative energy deposition by plasmonic nano-shells. The initial compression of the target pellet … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 34 publications
0
13
0
Order By: Relevance
“…The recent paper of Csernai et al (2018) commented here is even more problematic in this respect. The authors carried out calculations for an uncompressed ball heated by external radi-ation.…”
mentioning
confidence: 78%
See 2 more Smart Citations
“…The recent paper of Csernai et al (2018) commented here is even more problematic in this respect. The authors carried out calculations for an uncompressed ball heated by external radi-ation.…”
mentioning
confidence: 78%
“…According to these textbooks, the fusion efficiency (determined by the fusion cross-section and the thermal expansion) is given by a formula: w = ρR/(ρR + 6 g/cm 2 ). In case of a target of initially 1.062 g/cm 3 density with a radius of 640 μm -as proposed in the paper by Csernai et al (2018) -ρR ≈ 0.07 g/cm 2 which results in a burn fraction as low as ≈1%.…”
mentioning
confidence: 87%
See 1 more Smart Citation
“…In our previous studies, we have proposed a novel approach to promote uniform energy deposition and to ensure time-like ignition of fusion targets by doping them with metal nanoparticles [29]. Energy deposition increased by plasmonic nanoparticles allows the initial compression of the fusion target to be reduced, thus avoiding Rayleigh-Taylor instability that prevents the achievement of inertial confinement fusion [30].…”
Section: Introductionmentioning
confidence: 99%
“…It has also been shown that time-like ignition can be achieved via double-sided irradiation with short and intense laser pulses even at reduced compression, when the absorption of a target is improved by orders of magnitude due to embedded plasmonic core-shell nanoparticles [29]. Beside the energy deposition the charge separation on nanoparticles is also an important aspect, since its amplitude might be commensurate with that accompanying the laser wake field (LWF) dense plasma waves initiated by two intense counter-propagating laser pulses [31].…”
Section: Introductionmentioning
confidence: 99%